A CONTRIBUTION TO A THEORY OF PROBLEM SOLVING - DOSTAL, Jiri (Trends in education, 2015)
A theory of problem solving is, at the international scientific field, solved in a long term: mainly in psychology, but also in educational science (pedagogy), where the research of possibilities of the development of competences linked to the problem solving is now emphasized. The article therfore follows on works of the lead theorists in the field of psychology focused on the theory of problem solving. It contains an analysis of already published knowledge, compares it and evaluates it critically in order to create a basis that is corresponding to the current state of cognition. In its introductory part, it pursues a term problem and its definition. Furthermore, it pursues the problematic situations and circumstances that accompany the particular problem and appear during its solving. The main part of this article is an analysis of the problem solving process itself. It specifies related terms in detail, e.g. the ability to perceive the problem, the perceptibility of the problem, the willingness to solve the problem, the awareness of existence of the problem or strategies of problem solving.
Keywords: problem; problem solving; definition; psychology; education.